The Influence of Stress Coping And Genetics on Hypertension Status Age Range 36-45 Years in Sawit Health Centerboyolali Regency (Universitas Negeri Semarang, 2018)
Based on the observational and preliminary data from the Health Department of Boyolali, it is showed that the most non-communicable disease is hypertension with the total amount is 23.586 cases. The hypertension cases in Sawit Health Center is because of the less healthy lifestyle of the society due to the low attitude and behavior toward the prevention of hypertension. The aim of this study was to analyze the influence of stress coping and genetic on hypertension status at Sawit Health Center 2018. The present study used cross sectional study design. The sample of the study was 85 respondents that were taken in Sawit Health Center. Questionnaire was used as the instrument of the study in order to obtain the data of stress coping and genetic background of the respondents. The data analysis was done in multiple linear regressions. The results showed that (1) There is the influence of stress on hypertension status with p-value of 0.021Î± (0.05). (2) There is the influence of genetic on hypertension status with p-value of 0.000 Î± (0.05). People are suggested to do healthy life style, the Health Department and Local Government should do some health counseling comprehensively.